Determination of Cobalt in Seawater Using Neutron Activation Analysis after Preconcentration by Adsorption onto γ-MnO2 Nanomaterial - Van-Phuc Dinh; Ngoc-Chung Le; Ngoc-Tuan Nguyen; Quang-Thien Tran; Van-Dong Nguyen; Anh-Tuyen Luu; N. Quang Hung; Tran Duy Tap; Thien-Hoang Ho (Journal of Chemistry)
The γ-MnO2 nanomaterial has been used to adsorb cobalt in the seawater at Phan Thiet City, Binh Thuan Province, Vietnam. Its concentration is determined by using the neutron activation analysis (NAA) method at the Dalat nuclear research reactor. Factors affecting the uptake of cobalt on the γ-MnO2 material such as the pH, adsorption time, and initial cobalt(II) concentration are investigated. The irradiated experiment data are calculated using the K0-Dalat program. The results obtained show that the trace dissolved cobalt in Phan Thiet seawater is found equal to 0.25 ± 0.04 μg/L (n=5, P=95%) with the adsorption efficiency being higher than 95% (n=4, P=95%).